Constellations of state fragility: Improving international cooperation through analytical differentiation - Jasmin Lorch; Sebastian Ziaja; Jörn Grävingholt (German Institute of Development and Sustainability (IDOS), 2024)
State fragility has remained a pressing challenge for international security and development policymakers for more than two decades. However, international engagement in fragile states has often failed, in part due to a lack of understanding about what constitutes state fragility. Established quantitative models usually rank fragile states on one-dimensional scales ranging from stable to highly fragile. This puts states characterised by very different problems and dimensions of fragility into the same 'box'. Moreover, categorisations such as 'fragile', 'weak', 'failed' or 'collapsed' are increasingly rejected in the Global South, thereby hampering international development and security cooperation. The 'Constellations of State Fragility' model, developed at the German Institute of Development and Sustainability (IDOS), provides a more differentiated model to measure state fragility. It assesses state fragility along three continuous dimensions, assuming that state fragility is a continuous trait that affects all states to some degree: authority, capacity and legitimacy. These dimensions are not aggregated into a one-dimensional index. Instead, the model detects typical constellations across these dimensions. In so doing, it also accounts for the fact that states can perform very differently in different dimensions. Our analysis yields three main insights about what constitutes state fragility and how it can be addressed: first, state fragility, illiberalism, repression and human rights violations are interrelated; second, state fragility is not unique to the Global South, with negative trends also occurring in the Global North; and, third, differentiated, multi-dimensional models offer better starting points for addressing state fragility than one-dimensional ones. We conclude with four policy recommendations: • Improve analytical capacity by adopting a differentiated view of state fragility: International security and development policymakers would benefit from more fine-grained, differentiated assessments of state fragility. In addition, country-specific assessments of the specific local power constellations in which fragile state institutions are embedded are needed for devising adequate, context-sensitive measures. • Connect measures to address fragility with democracy protection and the protection of human rights: Illiberalism, human rights violations and repression correlate with state fragility. This also suggests that there is a close relationship between autocracy, autocratisation and fragility. Accordingly, measures to address fragility, democracy support and efforts to protect human rights must be better connected. This also implies doing 'no harm to democracy' (Leininger, 2023, p. 2). • Identify conditions under which state-building can (or cannot) be pursued: It would be fruitful if international security and development policymakers engaged in thorough discussions about the conditions under which state-building can be pursued. Where existing state institutions are legitimate, they should be supported. However, donor coherence and the capacity (and political will) of donors to commit resources to fragile states and to engage long-term are also important preconditions. State-building is both a costly and a long-term endeavour. • Learning across world regions: Patterns of state fragility can be highly similar, despite geographical distance. In particular, rising illiberalism and increasing attacks on civil liberties are global phenomena. Hence, policy decision-makers and civil society organisations (CSOs) seeking to counter fragility should engage in mutual learning across the North/South divide.
Keywords: 320; Fragile states; Weak states; Peace and security; Development; International cooperation; Democracy; Autocracy; Illiberalism; Repression; Human Rights